Original Statement: If x = 3, then x^2 = 9 (true)
Converse: If x^2 = 9, then x = 3 (false; this is half the story and x = -3 must be included)
Since the converse isn't completely true, we can't combine the two statements to get a biconditional.
Covert the problem into and equation using formulas
Answer:
x = 8
Step-by-step explanation:
7x + 2(6x + 9) = 170
2(6x + 9) = 12x + 18
7x + 12x + 18 = 170
19x = 152
152/19 = 8
x = 8
Answer:
50%
Step-by-step explanation:
duhh, sorry this one just very obvious